Syawir Education Response To The Digital Era: Challenges and Opportunities To Use Maktabah Syamilah - Pratiwi, Aprilia Yogi; Muhammad Bisri Ihwan (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
The digital era has brought a significant transformation in Syawir education, with Maktabah Syamilah as a digital library that offers wide accessibility to Islamic resources. This study aims to analyze Syawir's educational response to the digital era, using a qualitative approach through interviews and observations of teachers and students in several educational institutions. The results of the study show that Maktabah Shamilah improves interactivity and learning quality, but challenges such as limited digital skills and curriculum that has not been integrated with technology hinder optimal utilization. Therefore, digital skills training and curriculum reform that are responsive to technological developments are needed. With these steps, Syawir education can adapt well in the digital era, taking advantage of opportunities to increase students' understanding and involvement in Islamic teachings. This research is expected to provide insights for teachers, students, and educational institutions in optimizing the use of technology in religious learning.